The Impact of Working Capital Management and Credit Management Policies on the Financial Performance of Kosovo Banks - Caka, Elvira; Imeraj, Juliana; Gjonlleshaj, Gjon; Prenaj, Vlora (Ekonomika, 2025)
This study examines banking stability in Southeast Europe by analyzing both financial and institutional factors by using the Z-score as a key metric. On the basis of covering the period of 2012–2023, the research evaluates the impact of capital adequacy, lending rates, non-performing loans, rule of law, regulatory quality, control of corruption, judicial efficiency, and government integrity. The analysis combines static Ordinary Least Squares (OLS) and dynamic Generalized Method of Moments (GMM) methods on panel data. The key findings reveal that capital adequacy, non-performing loans, and regulatory quality positively influence banking stability, thereby suggesting the benefits of strong financial regulation. Conversely, control of corruption and weak government integrity negatively affect stability, highlighting institutional weaknesses. A novel aspect of the study lies in comparing the static and dynamic models: while OLS results show the rule of law as significant and positive and judicial effectiveness as negative, the GMM model finds these institutional variables largely insignificant. This divergence emphasizes the importance of using multidimensional empirical approaches to assess the complex interplay of governance and financial performance in the banking sector. The study ultimately demands strengthened legal and regulatory institutions to enhance banking stability in the region.
Keywords: Credit control; profitability; banking; public policies